Genetic association between Class II division 1 and division 2 malocclusions with PAX9 (rs8004560) gene polymorphism in a tertiary care hospital - Monika SHUKLA; Munish REDDY; Kritanjali SINGH; Ruchi SAINI; Pradeep RAGHAV; Kaynat NASSER; Nupur SHARMA; Aastha KAMRANI; Shehla RAFIQUE; Tanjula SHAIR (Dental Press Journal of Orthodontics)
ABSTRACT Objective: To assess whether there is any difference in the genetic association between Class II division 1 (div. 1) and division 2 (div. 2) malocclusions using PAX9 (rs8004560) gene single nucleotide polymorphism (SNP). Material and Methods: Sixty patients from the Orthodontics department of Subharti Dental College and Hospital (Meerut, India) were divided into two groups: Group 1 (Class II div. 1 malocclusion) and Group 2 (Class II div. 2 malocclusion). Then, 3 mL of blood was collected from each participant. DNA extraction was done, and Sanger Sequencing was performed from extracted DNA samples. Results: A statistically significant difference was found in the distribution of alleles among Class II div. 1 and Class II div. 2 malocclusions. The homozygous GG allele was the most prevalent among Class II div. 1 patients (76.7%), while the heterozygous AG allele was the most prevalent among Class II div. 2 patients (53.5%). Since GG was the most prevalent allele, it was used as a reference, and AA/AG were compared with GG to confirm the association. The results showed that individuals with the AG genotype seemed to be more susceptible to the development of skeletal Class II div. 2 malocclusion. Conclusion: The homozygous GG allele was the most prevalent among Class II div. 1 patients, while the heterozygous AG allele was the most prevalent among Class II div. 2 patients, suggesting that there could be a difference between the genetic association of both malocclusions.